Problem of Isis’s Qur’anic Interpretations and Claim of The Implementation of Sharia Law - Qaem Aulassyahied (IJISH (International Journal of Islamic Studies and Humanities), 2018)
This paper discusses the problem of ISISâ€™s Qurâ€™anic interpretations regarding the implementation of sharia law and the concept of jihad. It is essential to address this topic because the self-proclaimed Caliphate have claimed that their barbaric actions such as indiscriminate killing of civilians, plundering, and declaring other Muslims as apostates are based on Qurâ€™anic verses. They also consider these actions as part of the jihad to uphold sharia law. This paper argues that there are two main problems in ISISâ€™s Qurâ€™anic interpretations, namely (1) cherry picking Qurâ€™anic verses that support their causes. According to the principles of Qurâ€™anic exegesis (ushul al-tafsÄ«r), this method of interpretation is certainly not justified because it will lead to the partial understanding of the message of the Qurâ€™an; (2) attempting to enforce the sharia law without proper understanding of the law. As a result, ISISâ€™s implementation of sharia goes against the ultimate purposes of the sharia (maqÄsid al-sharÄ«â€™ah).